Effect of Permeation Enhancers on Buccal Absorption - Burgalassi, Susi; Chetoni, Patrizia; Dini, Laura; Najarro, Marcela; Monti, Daniela; Morelli, Paolo; Saettone, M. Fabrizio (Arzneimittelforschung, 2006)
This paper reports an investigation on matrices based on the mucoadhesive polymers hydroxypropylmethylcellulose and sodium alginate, intended for sublingual administration of 1 mg lorazepam (LZ, 7-chloro-5-(2-chlorophenyl)-1,3-dihydro-3-hydroxy-2H-1,4-benzodiazepin-2-one, CAS 846-49-1). The effect of different amounts of three permeation enhancers, cetylpyridinium chloride (CPC), polyethoxylated castor oil (PCO) and polyethylene glycol dodecyl ether (PGDE) on LZ permeation from the matrices was investigated using three models: (a) cultured monolayer of human buccal epithelial cells; (b) hamster cheek pouch mucosa in vitro, and (c) buccal administration to rabbits in vivo. In the first two models the presence of promoters, except when present at the higher concentrations, increased the drug permeation rate. The permeation-reducing effect was rationalized on the basis of micellar complexation of the drug. In the living rabbit (c) model, only CPC at the highest tested concentration was moderately active, while in the cultured cell model activity differences among the enhancers were less evident. Different effects of the promoters in the ex vivo and in vivo models were tentatively explained on the basis of the structural characteristics of the absorbing membranes. The present study, while confirming the efficacy of CPC as promoter in models involving biological membranes, does not provide conclusive data on the validity of the cultured cells model for assessment of buccal drug absorption.
Keywords: Buccal cell line, rabbit; Buccal matrices; CAS 846-49-1; Hamster cheek pouch; Lorazepam; Permeation enhancers